Epidemiological situation on tuberculosis among the children and teenage population 159 (review of literature) - V. V. Dolgikh; N. S. Khantaeva; Y. N. Yaroslavtseva; D. V. Kulesh (Acta Biomedica Scientifica, 2013)
Tuberculosis is nowadays one of the most actual problems of world public health, service. According to the data of WHO, one third of world's population is infected, with tuberculosis microbacteria. Every year 2-3 millions of people die because of tuberculosis. During last years in Russia tuberculosis morbidity increased 2,3 times, mortality - 1,9 times and prevalence - 4 %. Aggravation of epidemiological situation on tuberculosis is characterized by increase of morbidity among all age groups and especially among the children. In Irkutsk region epidemiological situation on tuberculosis is still intensive. Main reasons of unsatisfactory indices of tuberculosis in Irkutsk region are: presence of significant reservoir of tuberculosis infection among the population. of the region; significant level of prevalence of HIV-infection; unsatisfactory material and technical base of antituberculous institutions of the region; personnel deficiency in antituberculous institutions; insufficient level of preventive measures in foci of tuberculosis infection; absence of modern, medical informational system in antituberculous institutions of the region. To optimize the situation at the development of antituberculous measures it is necessary to take into account regional peculiarities of epidemic situation, to realize control and. organization of an aid. for children from the foci of tuberculosis infection and. to carry out controlled chemical prophylaxis in sanatorium conditions.